Contrast enhancement kinetics of normal breast parenchyma in dynamic MR mammography: effects of menopausal status, oral contraceptives, and postmenopausal hormone therapy - Hegenscheid, Katrin; Schmidt, Carsten O.; Seipel, Rebecca; Laqua, René; Ohlinger, Ralf; Hosten, Norbert; Puls, Ralf (European radiology, 2012)
Objectives To investigate effects of menopausal status, oral contraceptives (OC), and postmenopausal hormone therapy (HT) on normal breast parenchymal contrast enhancement (CE) and non-mass-like enhancing areas in magnetic resonance mammography (MRM). Methods A total of 459 female volunteers (mean age 49.1 ± 12.5 years) underwent T1-weighted 3D MRM 1–5 min after bolus injection of gadobutrol. Quantitative analysis was performed in normal breast parenchyma by manually tracing regions of interest and calculating percentage CE. Semiquantitative analysis was performed in non-mass-like enhancing areas, and signal intensity changes were characterised by five predefined kinetic curve types. The influence of OC ( n = 69) and HT ( n = 24) on CE was studied using random effects models. Results Breast parenchymal enhancement was significantly higher in premenopausal than in postmenopausal women ( P < 0.001). CE decreased significantly with the use of OC ( P = 0.01), while HT had negligible effects ( P = 0.52). Prevalence of kinetic curve types of non-mass-like enhancement differed strongly between pre- and postmenopausal women ( P < 0.0001), but was similar in OC users and non-OC users ( P = 0.61) as well as HT users and non-HT users ( P = 0.77). Conclusions Normal breast parenchymal enhancement and non-mass-like enhancing areas were strongly affected by menopausal status, while they were not affected by HT use and only moderately by OC use. Key Points • Breast parenchymal enhancement at MR mammography is stronger in premenopausal than postmenopausal women. • The prevalence of strong enhancing non-mass-like areas is greater before menopause. • Such enhancing non-mass-like areas may impair lesion detection in premenopausal women. • Breast parenchymal enhancement is only marginally affected by hormone use. • Discontinuation of hormone use before MR mammography may be unnecessary.